Collection of test for topical diagnostic for practical employments for the students of the 4th course of II international faculty - Kozyolkin, O. A.; Vizir, I. V.; Sikorskay, M. V.; Козьолкін, Олександр Анатолійович; Візір, Ірина Володимирівна; Сікорська, Марина Володимирівна (Запорізький державний медичний університет, 2019)
Further progress of higher medical education requires implementing new forms of both teaching methods and knowledge control. These new forms intensify the learning process and develop student’s practical diagnostic. In the collection of tasks on topical diagnostics test tasks for practical exercises are presented to prepare for modular tests with answer standards the collection can be used both for independent work of students and teachers in the process of practical exercises.